Predictors of perceived Higher Order Thinking Skills (HOTS) among diploma and undergraduate students / Nurul Emyza Zahidi … [et al.] - Zahidi, Nurul Emyza; Jama, Siti Ramizah; Abdul Halim, Bushra; Fuzi, Siti Fairus; Zainudin, Siti Nursyahira; Jusoh, Nordianah; Wan Hassan, Wan Hartini (Faculty of Computer and Mathematical Sciences, 2021)
The study determines the relationship between perceived higher order thinking skills (HOTS) of diploma and bachelor’s degree students and the academic performance in the university. Samples are selected from all full-time students pursuing study in Universiti Teknologi MARA Cawangan Melaka (UiTMCM) using purposive sampling technique. Samples consist of 425 (60.9%) students of semester 1 and 273 (39.1%) students of semester 2 and higher from seven faculties pursuing studies at diploma and bachelor’s degree study level. Results reveal that perceived analyzing, evaluating, creating thinking skills and overall HOTS among students are at moderate level. Male students perceive that they are significantly more evaluative and creative than female students. Diploma and bachelor’s degree students show they are at the same moderate level in analyzing, evaluating, creating thinking skills and overall HOTS. Family permanent residents (rural, sub-urban or urban) are shown to have no effect on analyzing, evaluating, creating thinking skills and overall HOTS among students. Socio-economic status of students from family income RM8000 and above are proven to be significantly more creative and having higher overall HOTS level than those students from lower family income group. There is no significant difference in intake qualification (Sijil Pelajaran Malaysia (SPM), diploma or Sijil Tinggi Pelajaran Malaysia (STPM)/Asasi/Matriculation) of students on analyzing, evaluating, creating thinking skills and overall HOTS. However, students of July/September intake perceived significantly higher creating thinking skills and overall HOTS compared to students of March/November intake. Kemahiran Berfikir Aras Tinggi (KBAT) experienced during schools are found to be significantly influencing the perceived evaluating, creating thinking skills and overall HOTS among students. Lastly, perceived overall HOTS only explains 2.8% of the variance in CGPA of students.